PSIKOSOSIAL ANAK DALAM KUMPULAN DONGENG BAGAI BUMI BERHENTI PERPUTAR DAN SEJUTA WARNA PELANGI KARYA CLARA Ng - Sri Utami Affrilia Dewi (EDU-KATA, 2020)
The purpose of this study is to: Describe the Psychosocial Form of1) Trust versus Suspicion. 2) Autonomy versus Shyness and Hesitation. 3) Initiative versus Error form. 4) Integrity versus Despair in a collection of Tales Like Earth Stop Rotating and Million Colors of Rainbow by Clara Ng.To understand and appreciate literary works (dogeng), researchers use a formalist / New Criticism approach, that is, researchers pay attention to the complexity of the structure and constructs of the work. A work is judged by its success and stability through its form, which is to see the integrity of its structure by examining the relationships and intertwined relationships of its supporting elements. According to the formalist approach, literary text is an object that must be analyzed in order to find its meaning. In short, the purpose of the formalist approach is to find out whether the contents of a work and how the content is delivered (Sarumpaet, 2010: 39).The results of the study are as follows. 1) I'm so scared to hear the words 2) It's great to go home to Indonesia 3) And the country is very far from Indonesia 4) Star, stay shining so Pipi know Mother is okay up there.